Gamma rays induced enhancement in the phytonutrient capacities of tomato (Solanum Lycopersicum L.) - Kantoğlu, K. Yaprak; İç, Erhan; Özmen, Dilan; Bulut, F. Şebnem; Ergun, Ece; Kantoğlu, Ömer; Özçoban, Mustafa (Frontiers in Horticulture, 2023)
One of the most important problems for the field-grown Ayaş tomato (Solanum lycopersicum Ayas population), which is preferred for consumption in Central Anatolia because of its aromatic taste, is that the shelf life is short because of insufficient fruit firmness. Therefore, a study was initiated to develop high-quality lines and variety candidates through mutation breeding in the current Ayaş population. In this study, the effective mutation dose (EMD50) was found to be 150 Gy for seeds using a Cobalt-60 gamma ray source. The main mutant population was generated by applying EMD50. During the study, mutant lines selected by following the classical mutation breeding stages were evaluated in terms of yield and quality traits (antioxidant content, total soluble solid amount, fruit firmness, Brix, etc.) starting from the M4 stage. One of our aims was to determine and improve the phytonutrient content of field-grown tomatoes. The fruits of selected lines at the M4 stage were extracted by liquidliquid partition and accelerated solvent extraction techniques and analyzed by High Performance Liquid Chromatography (HPLC) in this study. It was found that 28 of the 29 mutant lines were significantly different from the control and mutant lines. Mutant lines 9-22, 8-90, 8-135, and 8-127 were determined to be the most promising for commercialization.